Measuring supersymmetry with heavy scalars - Turlay, Emmanuel; Lafaye, Remi; Plehn, Tilman; Rauch, Michael; Zerwas, Dirk (Journal of physics. G, Nuclear and particle physics, 2011)
Supersymmetry with heavy scalars is a model where, at the LHC we have to rely on rate measurements to determine the parameters of the underlying new physics. For this example we show how to combine rate measurements with kinematic endpoints properly, taking into account statistical, systematic and theoretical uncertainties. Provided we observe a sizeable number of events, the LHC should be able to determine many model parameters with small enough error bars to, for example, test unification patterns.
Gesehen am 30.11.2022